2023
DOI: 10.1038/s41588-023-01323-z
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of endometriosis and comorbidity with other pain and inflammatory conditions

Abstract: Endometriosis is a common condition associated with debilitating pelvic pain and infertility. A genome-wide association study meta-analysis, including 60,674 cases and 701,926 controls of European and East Asian descent, identified 42 genome-wide significant loci comprising 49 distinct association signals. Effect sizes were largest for stage III/IV disease, driven by *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 100 publications
5
93
2
Order By: Relevance
“…Interestingly, BMP2 levels were decreased in the peritoneal fluid of women with endometriosis 111 . Recent large-scale genome-wide association studies (GWAS) also identified BMPR2 as one of the endometriosis risk loci 67 . In women with recurrent implantation loss, BMP7 was identified to harbor a deleterious mutation that was predicted to be disease-causing 112 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BMP2 levels were decreased in the peritoneal fluid of women with endometriosis 111 . Recent large-scale genome-wide association studies (GWAS) also identified BMPR2 as one of the endometriosis risk loci 67 . In women with recurrent implantation loss, BMP7 was identified to harbor a deleterious mutation that was predicted to be disease-causing 112 .…”
Section: Discussionmentioning
confidence: 99%
“…It was identified 42 genome-wide significant loci with 49 distinct signals that had larger effect size for advanced stage endometriosis, explaining up to 5.01% of disease variance. Furthermore, the authors found an interesting genetic correlation between endometriosis and pain and inflammatory conditions, which may demonstrate the genetic basis of shared pathogenesis (Rahmioglu et al, 2023).…”
Section: Introductionmentioning
confidence: 91%
“…In a further meta-analysis, Sapkota et al ( 38 ) identified five novel endometriosis risk loci exhibiting significance in GWA, namely fibronectin 1 ( FN1 ), Coiled-coil domain containing 17 ( CCDC170 ), estrogen receptor 1 ( ESR1 ), spectrin repeat-containing nuclear envelope protein 1 ( SYNE1 ) and follicle-stimulating hormone beta subunit ( FSHB ), with all of them being involved in sex steroid hormone pathways. In the largest GWAS and replication meta-analysis of endometriosis that has been performed to date, enrolling 60,674 cases and 701,926 controls of European and East Asian ancestry, 42 genome-wide significant loci were identified, including 31 novel ones, such as ADP ribosylation factor like GTPase 14 effector protein ( ARL14EP ), Bcl-2-modifying factor ( BMF ), homeobox A10 ( HOXA10 ), long intergenic non-protein coding RNA 629 ( LINC00629 ), alpha 1–3-N-acetylgalactosaminyltransferase and alpha 1–3-galactosyltransferase ( ABO ), bassoon presynaptic cytomatrix protein ( BSN ), PDZ and LIM domain 5 ( PDLIM5 ), potassium channel tetramerization domain containing 9 ( KCTD9 ), MLLT10 histone lysine methyltransferase DOT1L cofactor ( MLLT10 ), actin like 9 ( ACTL9 ) and inhibitor of DNA binding 4 ( ID4 ) ( 39 ). The majority of SNPs exhibited larger effect sizes for stage III/IV disease, and when combined, they explained 5.61% of stage III/IV disease variance.…”
Section: Genetics Of As and Endometriosismentioning
confidence: 99%
“…Accumulating evidence has indicated that inflammation plays a critical role in pathologic bone formation in patients with AS ( 52 ). Considering that AS represents a disease that is associated with chronic inflammation, it is characterized by the key role of dendritic cells, natural killer (NK) cells, macrophages and cells of adaptive immunity, with all these cells producing a variety of cytokines that lead to the development of the disease ( 39 ). Thus, elevated levels of pro-inflammatory cytokines, including IL-1B, IL-6, IL-8, IL-10, IL-17, IL-21 and IL-23 have been observed in patients with AS compared with normal subjects, whereas increased levels of interferon (IFN)-γ and TNF-α have been also reported in some patients as a result of aggressive inflammatory responses ( 5 ).…”
Section: Influence Of Autoimmunity Angiogenesis and Inflammation In A...mentioning
confidence: 99%